Pentingnya Pemahaman Dan Pengetahuan Hukum Perusahaan Bagi Pelaku Usaha Dalam Pendirian Perseroan Terbatas - Adelia, Farah (Peneliti.net, 2024)
This journal explains the law of Companies in Indonesia with the aim of achieving both understanding and knowledge of Company law in Indonesia in the hope that it can help prospective business actors in establishing their companies in accordance with applicable regulations and laws in Indonesia. This journal also discusses the importance of understanding and knowledge of Company law for business actors in establishing or forming a Company. This journal also explains basic matters related to company law such as what is company law, legal sources from company law, company forms to company establishment.